2021
DOI: 10.7759/cureus.16236
|View full text |Cite
|
Sign up to set email alerts
|

Primary Esophageal Tuberculosis With Dysphagia

Abstract: Tuberculosis is a common infection caused by Mycobacterium tuberculosis. Tuberculosis can affect many organ systems of the human body including the gastrointestinal tract. Esophageal involvement of tuberculosis is however rare.A 60 years old male from Nepal with an occupational history suggestive of exposure to tuberculosis presented with dysphagia. He did not have any other complaints and his physical examination was unremarkable. An upper gastrointestinal endoscopic examination revealed an esophageal ulcer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…The analysis indicated that all the traits are highly co-related with each other. No significant correlation was found previously between these traits (Ram Poudel et al, 2021). Under HS, RL and RW were significantly correlated to SL and SW.…”
Section: Hsi Of Historical Wheat Cultivarscontrasting
confidence: 57%
“…The analysis indicated that all the traits are highly co-related with each other. No significant correlation was found previously between these traits (Ram Poudel et al, 2021). Under HS, RL and RW were significantly correlated to SL and SW.…”
Section: Hsi Of Historical Wheat Cultivarscontrasting
confidence: 57%
“…TB of the esophagus often affects its middle section [6]. TB of the esophagus typically results from direct extension from surrounding structures, such as mediastinal lymph nodes and pulmonary sites [2]. It is hypothesized that the accumulation of swallowed sputum or infected milk products is one of the reasons for GI TB [7].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, tuberculosis (TB) is the largest cause of death worldwide from a single infectious disease agent [ 1 ]. In 2019, around 10 million people contracted tuberculosis worldwide, and an estimated 1.2 million HIV-negative people died from TB [ 2 ]. It affects the respiratory system predominately.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations